GAMIFICATION IN THE DEVELOPMENT OF COGNITIVE SKILLS AND LEARNING FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) - Marques, Michele Bitencourt; Nunes, Paula de Castro (Seven Editora, 2025)
The clinical picture of children with Autism Spectrum Disorder (ASD) is characterized by deficits in social interaction and communication, as well as repetitive interests and activities. Technology is an essential component in the education of students with special needs, as it allows them to access tasks that would otherwise be out of their reach. The general objective was to investigate the contribution of gamification in the development of cognitive skills and learning of students with Autism Spectrum Disorder (ASD). The most relevant results indicate that the interaction with digitized activities allowed concepts, such as mathematics, to be elaborated in a more accessible and attractive way for students, overcoming the barriers found in non-digital environments. The adoption of gamification as a teaching method has contributed significantly to the development of cognitive and social skills, highlighting the potential of these technologies to promote more inclusive and personalized learning. Despite the limitations, the results obtained reinforce the feasibility of using digital technologies in the teaching of students with ASD, aligning with the need for pedagogical innovations that meet the specificities of this audience. Thus, by adopting technologies as teaching tools, the education of students with ASD can become more dynamic, accessible, and effective.DOI: https://doi.org/10.56238/sevened2024.037-160